UNLOCKING COMMUNICATION DYNAMICS: ILLOCUTIONARY SPEECH ACTS ANALYSIS IN THE "KOS MAS ADAM" WHATSAPP GROUP - Lusianto, Feri; Prasetyo, Yudy; Sari, Endah Alam (Jurnal Visi Ilmu Pendidikan, 2024)
This study explores the dynamics of speech acts within communication processes, with a focus on Searle"™s classification of illocutionary acts into five categories: assertive, referential, commissive, expressive, and declarative. It aims to provide a descriptive overview of illocutionary acts in the "Kos Mas Adam" WhatsApp group and identify their prevalence. Employing a qualitative descriptive approach, data analysis utilized heuristic analysis techniques. The study reveals various illocutionary speech acts in the group discussions, with assertive speech being the most common (9 data), followed by expressive (12 data) and directive (4 data). Notably, commissive speech is scarce, with only one instance, and declarative with two. These findings underscore the uneven distribution of illocutionary acts within the WhatsApp group "Kos Mas Adam", with implications for understanding online discourse dynamics. Future research may explore strategies for promoting a more balanced use of illocutionary speech acts in online group interactions.